ENDOSCOPIC ENDONASAL TRANS-SPHENOIDAL SURGERY IN PATIENTS WITH MACRO-ADENOMA EXTENT OF SURGICAL RESECTION AND RECURRENCE RATE - Zia Ur Rahman,; Muhammad Idris Khan,; Muhammad Aamir, (Journal of Ayub Medical College Abbottabad, 2024)
Background: EETA has been employed for skull base tumors especially macro-adenomas, for the last decade in our setup. Here we are sharing our experience with the EETA for patients with micro-adenomas in terms of extent of tumor resection and its recurrence. The objective was to assess endoscopic endonasal trans-sphenoidal surgery in patients with macro-adenoma for extent of surgical resection and recurrence rate. Methods: This descriptive case series study was carried out from May 2021 till April 2023. Male and female patients with macroadenoma were enrolled which was diagnosed with contrast enhanced volumetric MRI brain. EETA and resection was performed. Extent of resection recurrence was confirmed on post-op MRI and follow up at 6 months respectively. Results: A total of 58 patients were enrolled. Mean age of the patients was 47.51 ± 7.93 years and male to female ratio was 1.3: 1. 42 (72.4%) tumors were non-functional. Somatotropin releasing tumor was the most common functional tumor (n = 09, 15.5%). Total resection was performed in 49 (84.4%) patients. Recurrence was observed in 09 (15.6%) cases. Conclusion: EETA has been shown to be a safe and effective technique for the resection of macroadenoma of the skull base.